'n Ondersoek na die persoonlike ervaring van bevoegdheid van studentvroedvroue in die uitvoer van episiotomie-hegtings - M. E. Bester; H. A. Lamprecht (AOSIS, 1995)
A nan-experimental, descriptive study was conducted to determine the knowledge and efficiency of student midwives in the performing of episiotomy repairs. A questionnaire was administered to 50 students front the two universities and affiliated colleges in the Western Cape. Sixty percent (N = 3O) of the respondents regarded themselves as efficient. However, only one of these respondents had all the necessary knowledge concerning perineal repairs with 15 (50%) of these respondents' knowledge that could be considered as insufficient. Fifty-four percent of the respondents (N = 27) considered it necessary to repair more than 3 episiotomies in order to feel confident.